Barriers and facilitators of rendering HIV services by community health workers in sub-Saharan Africa: a meta-synthesis protocol - Tivani Phosa Mashamba-Thompson; Elizabeth Lutge; Gugulethu Eve Khumalo; Praba Naidoo (BMJ Open)
Introduction In sub-Saharan Africa (SSA), Human Immunodeficiency Virus (HIV) is the leading cause of morbidity and mortality. Community healthcare workers (CHWs) worldwide have been reported to be effective in strengthening the HIV programme by providing services such as adherence support, HIV education and safe sex education as part of their roles. The main aim of this meta-synthesis is to synthesise qualitative evidence on studies that have been conducted in SSA countries to understand the barriers to and facilitators of providing HIV services by CHWs across all settingsMethods and analysis This meta-synthesis will be guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses. An initial search was conducted on 15 November 2019 for studies published between 2009 and 2019 using the population exposure outcome nomenclature. We searched the EBSCOHost- (ERIC; Health Source-Nursing/Academic Edition), Google Scholar and PubMed databases for the relevant studies. The Ritchie and Spencer framework will be used for data synthesis and the Supporting the Use of Research Evidence Framework analysis will be used to analyse data. We will conduct critical appraisal on selected studies using the Qualitative Assessment and Review Instrument to limit risk of bias.Ethics and dissemination This review does not involve any human participants and therefore ethical approval will not be required. We will publish the protocol as well as the findings in any relevant journal and various media namely conferences; symposia, local and international health stakeholders.PROSPERO registration number CRD42020160012.Conclusion Evidence from this review will provide synthesised evidence to the utilisation of CHWs in HIV services in SSA.